Identification and initial characterisation of a protein involved in Campylobacter jejuni cell shape. (March 2017) - Esson, Diane; Gupta, Srishti; Bailey, David; Wigley, Paul; Wedley, Amy; Mather, Alison E.; Méric, Guillaume; Mastroeni, Pietro; Sheppard, Samuel K.; Thomson, Nicholas R.; Parkhill, Julian; Maskell, Duncan J.; et al.
Abstract: Campylobacter jejuni is the leading cause of bacterial food borne illness. While helical cell shape is considered important for C. jejuni pathogenesis, this bacterium is capable of adopting other morphologies. To better understand how helical-shaped C. jejuni maintain their shape and thus any associated colonisation, pathogenicity or other advantage, it is first important to identify the genes and proteins involved. So far, two peptidoglycan modifying enzymes Pgp1 and Pgp2 have been shown to be required for C. jejuni helical cell shape. We performed a visual screen of ∼2000 transposon mutants of C. jejuni for cell shape mutants. Whole genome sequence data of the mutants with altered cell shape, directed mutants, wild type stocks and isolated helical and rod-shaped 'wild type' C. jejuni, identified a number of different mutations in pgp1 and pgp2, which result in a change in helical to rod bacterial cell shape. We also identified an isolate with a loss of curvature. In this study, we have identified the genomic change in this isolate, and found that targeted deletion of the gene with the change resulted in bacteria with loss of curvature. Helical cell shape was restored by supplying the gene in trans . We examined the effect of loss of the gene on bacterial motility, adhesion and invasion of tissue culture cells and chicken colonisation, as well as the effect on the muropeptide profile of the peptidoglycan sacculus. Our work identifies another factor involved in helical cell shape. Highlights: A C. jejuni isolate with a loss of curvature was identified. A targeted gene deletion of CJJ81176_1105 in 81–176 and CJM1_1064 in M1 were created. Defined gene deletion mutants of CJJ81176_1105 and CJM1_1064 alter C. jejuni motility and interaction with Caco-2 cells. Defined gene deletion mutant of CJM1_1064 does not alter C. jejuni colonisation of chickens.